Demokrasi Pemerintahan dan Etika Revolusi dalam Bingkai Fiqh Politik Islam - Andi Ahsan Taqwim; Abd. Wahid Haddade; Patimah P (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The study of Islamic political jurisprudence (fiqh siyasah) has become increasingly relevant in addressing the dynamics of modern governance characterized by democratization, demands for justice, and the emergence of political change and revolutionary movements. This paper aims to analyze the concept of democratic governance and the ethics of revolution within the framework of Islamic political jurisprudence, emphasizing core Islamic principles such as shura (consultation), justice, public welfare (maslahah), and amar ma‘ruf nahi munkar (enjoining good and forbidding evil). This research employs a qualitative normative approach through a literature review of classical and contemporary sources in Islamic law. The findings indicate that fiqh siyasah functions as a normative instrument regulating the relationship between rulers and the people, emphasizing trust (amanah), justice, and moral responsibility in the exercise of power. Fiqh at-thawrah in Islam is not understood as an unconditional legitimation of rebellion, but rather as an ethical framework for socio-political change that must consider the objectives of Islamic law (maq??id al-shar?‘ah) and avoid greater harm (mafsadah). Democracy, from the perspective of Islamic political jurisprudence, is acceptable as an ijtih?d-based mechanism insofar as it serves as a means to realize justice, public participation, and accountability of authority, without negating the sovereignty of divine law. Meanwhile, the system of governance in Islam is flexible and contextual, provided that it remains grounded in the principles of shura, justice, and public welfare. Thus, Islamic political jurisprudence offers an ethical and normative paradigm for the development of just, democratic, and morally grounded governance in the modern era.